The Evaluation of Science Module Implementation of Teaching for Change Community Project - Han, Crispina Gregory K (SOSIOHUMANIKA, 2015)
ABSTRACT: This community development project was carried out at a Primary School located at Kota Belud, Sabah, Malaysia.Â The aim is to construct and implement these modules for Year 1 to Year 6 students to master the skills in English, Mathematics, and Science. The purpose of the process evaluation is to identify and monitor continuously various elements of project operation.Â The CIPP (Context, Input, Process, and Product) Model of D.L. Stufflebeam (1985) was used to evaluate the implementation of the project.Â This study focuses on the process evaluation of the Science module implementation.Â A qualitative study was conducted. A purposive sample of twelve informants participated in the study. Data was garnered using a focus group discussion interview. Several themes were identified from the final findings of this study. Emerging themes were development and enhancement of the teaching and learning skills. Development and enhancement of teaching focuses on module construction and application, creativity application, SCL (Student Centered Learning) strategy, multimedia approach, class control skill, confidence level, peers learning, teacher responsibility, time organization, lesson plan preparation, and evaluation focused on the design illuminating the procedures and strengths weaknesses. Overall, the module for Science has shown positive outcomes.Â KEY WORD: Process evaluation, CIPP model, science module, community development project, and positive outcomes.RESUME: âPenilaian Pelaksanaan Modul Sains dalam Projek Komuniti Mengajar untuk Perubahanâ. Projek pembangunan masyarakat ini telah dijalankan di sebuah Sekolah Rendah yang terletak di Kota Belud, Sabah, Malaysia. Tujuannya adalah untuk membina dan melaksanakan modul untuk pelajar Tahun 1 hingga Tahun 6 bagi menguasai kemahiran dalam Bahasa Inggeris, Matematik, dan Sains. Tujuan penilaian proses ini adalah untuk mengenal pasti dan memantau secara berterusan pelbagai elemen operasi projek. Model KIPP (Konteks, Input, Proses, dan Produk) daripada D.L. Stufflebeam (1985) telah digunakan untuk menilai pelaksanaan projek. Kajian ini memberi tumpuan kepada penilaian proses bagi pelaksanaan modul Sains. Kajian telah dilaksanakan dengan menggunakan kaedah kualitatif. Persampelan bertujuan digunakan ke atas dua belas peserta yang telah mengambil bahagian dalam kajian ini. Data diperolehi dengan menggunakan perbincangan temubual kumpulan berfokus. Beberapa tema dikenal pasti daripada dapatan kajian. Tema utama ialah pembangunan dan peningkatan kemahiran pengajaran dan pembelajaran. Pembangunan dan peningkatan pengajaran memberi tumpuan kepada pembinaan modul dan aplikasi, aplikasi kreativiti, strategi PBP (Pembelajaran Berpusatkan Pelajar), pendekatan multimedia, kemahiran mengawal kelas, tahap keyakinan, pembelajaran sesama rakan, tanggungjawab guru, organisasi masa, penyediaan rancangan pengajaran, dan penilaian yang memberi tumpuan kepada kekuatan dan kelemahan pembangunan modul. Secara keseluruhan, modul Sains telah menunjukkan hasil yang positif.KATA KUNCI: Proses penilaian, model CIPP, modul sains, projek pembangunan masyarakat, dan hasil yang positif.About the Author: Crispina Gregory K. Han is a Lecturer at the Science and Mathematics Education Program, Faculty of Psychology and Education UMS (Malaysia University of Sabah), Jalan UMS, 88400 Kota Kinabalu, Sabah, Malaysia. For academic interests, the author is able to be contacted via mobile phone at: +60128666176 or e-mail at: crispinagregory@gmail.comHow to cite this article? Han, Crispina Gregory K. (2015). âThe Evaluation of Science Module Implementation of Teaching for Change Community Projectâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(2) November, pp.267-280. Bandung, Indonesia: Minda Masagi Press and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (October 20, 2015); Revised (October 30, 2015); and Published (November 30, 2015).